Simultaneous enhancement of energy storage and luminescent performances in SrSmxAgNaNbZrxO multifunctional ceramics - Yan Wang; Suwan Li; Yihan Tong; Zhiwei Feng; Xiaolian Chao; Zupei Yang; Pengfei Liang; Jiangbo Lu; Lingling Wei (Journal of Advanced Dielectrics)
Rare earth-doped ferroelectric (FE) ceramics have attracted much attention due to their great potential application for novel multifunctional optical-electro devices. This study successfully devised and fabricated tungsten bronze Sr[Formula: see text]SmxAg[Formula: see text] Na[Formula: see text]Nb[Formula: see text]ZrxO[Formula: see text] ceramics, demonstrating exceptional energy storage and luminescent properties suitable for multifunctional capacitors. Effects of co-doping Sm[Formula: see text] and Zr[Formula: see text] in A and B sites on the phases structure, FE, energy storage and photoluminescence properties of Sr[Formula: see text]SmxAg[Formula: see text]Na[Formula: see text]Nb[Formula: see text]ZrxO[Formula: see text] ceramics were systematically investigated. Through employing various collaborative optimization strategies, encompassing the refinement of ceramic grains, the induction of nanodomain generation and the incorporation of large bandgap components, enhancement of breakdown strength and regulation of constructing relaxor FEs were achieved. Encouragingly, the high-performance multifunctional materials with remarkable recoverable energy storage metrics ([Formula: see text] 3.72[Formula: see text]J/cm3, [Formula: see text] 82.7%), brilliant red-orange light emission and distinguished frequency and temperature stabilities within specific ranges were obtained in Sr[Formula: see text]Sm[Formula: see text]Ag[Formula: see text]Na[Formula: see text]Nb[Formula: see text]Zr[Formula: see text]O[Formula: see text] ceramics. Besides, the multifunctional ceramics demonstrated a high-power density (68.1[Formula: see text]MW/cm[Formula: see text], a substantial current density (908.1[Formula: see text]A/cm[Formula: see text] and a fast discharge time (51[Formula: see text]ns) at 190[Formula: see text]kV/cm. These findings suggest that the designed Sr[Formula: see text]SmxAg[Formula: see text]Na[Formula: see text]Nb[Formula: see text]ZrxO[Formula: see text] ceramics hold promise as candidate materials for dielectric capacitors.